Marketing Komunikasi Wisata Pantai Nglambor(Studi Deskriptif Kualitatif Marketing Komunikasi Wisata Pantai Nglambor Oleh Bintang Nglambor Snorkeling Melalui Akun Instagram pantai_nglambor) - Libriyanto, Firmada; , Dr. Edy Purwo Saputro, SE., M.Si (2017)
The existences of organization in tourism area through social media is a new method or innovation in the development of tourism field. In this modern era, it is easy to spread or exchange information, even promotion, in social media. One of the media used today is instagram. Instagram is used by the management of tourism object of Bintang Nglambor Snorkeling to promote this site. This research aimed to describe tourism promotion conducted by Bintang Nglambor Snorkeling through Instagram. This research applied a qualitative-descriptive method. The object of this research was the account of @pantai nglambor used by Bintang Nglambor Snorkeling to make promotion. Data were collected using semi-structured interview and the analysis used source triangulation. To complete data, the researcher took the admin of the instagram, local citizen, and also the visitors. The results of the study showed that in promoting this area, there were external and internal factors which were strength, weakness, threat, and opportunity. Instagram is a kind of social media which gave a lot of strengths and opportunities to Bintang Nglambor Snorkeling in doing tourism promotion such as, easy access to spread information. There were many features in instagram which was supportive, effective and can maintain national economy. By using instagram in the process of promotion, it could be easily attract people to visit Nglambor beach. However, instagram also brought weakness and threat to Bintang Nglambor Snorkeling in doing promotion.